Diagnosis and Staging of Metabolic Dysfunction-Associated Steatotic Liver Disease Using Biomarker-Directed Aptamer Panels - Mikkel B. Kjær; Asger G. Jørgensen; Søren Fjelstrup; Daniel M. Dupont; Claus Bus; Peter L. Eriksen; Karen L. Thomsen; Jeyanthini Risikesan; Søren Nielsen; Charlotte W. Wernberg; Mette M. Lauridsen; Elisabetta Bugianesi; et al. (Biomolecules, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) affects one-third of adults globally. Despite efforts to develop non-invasive diagnostic tools, liver biopsy remains the gold standard for diagnosing metabolic dysfunction-associated steatohepatitis (MASH) and assessing fibrosis. This study investigated RNA aptamer panels, selected using APTASHAPE technology, for non-invasive MASLD diagnosis and fibrosis stratification. Aptamer panels were selected in a cohort of individuals with MASLD (development cohort, n = 77) and tested in separate cohorts: one with MASLD (test cohort, n = 57) and one assessed for bariatric surgery (bariatric cohort, n = 62). A panel distinguishing MASLD without steatohepatitis from MASH accurately stratified individuals in the developmentcohort (AUC = 0.83) but failed in the test and bariatric cohorts. It did, however, distinguish healthy controls from individuals with MASLD, achieving an AUC of 0.72 in the test cohort. A panel for fibrosis stratification differentiated F0 from F3–4 fibrosis in the development cohort (AUC = 0.68) but not in other cohorts. Mass spectrometry identified five plasma proteins as potential targets of the discriminative aptamers, with complement factor H suggested as a novel MASLD biomarker. In conclusion, APTASHAPE shows promise as a non-invasive tool for diagnosing and staging MASLD and identifying associated plasma biomarkers.